THE THE RISE OF RAINBOW VILLAGE: OPTIMIZING AESTHETICAL PROGRAM TO ACCELERATE SANITATION ACCESS - Defi, Larasati Putri; Kusumayanti, Intan; Wika Maulany Fatimah; Sarli, Prasanti Widyasih; Soewondo, Prayatni (GEOMATE Journal, 2022)
Fulfilling basic needs for clean water and sanitation is still a challenge faced by Indonesia in achieving SDGs targets. In 2019, national access to basic sanitation was 77.83%, whereas in Java Province only reached 66.25% of its population. The high rate of urbanization increases the number of slum areas in big cities in Indonesia. One of the problems commonly found in slum areas is the lack of sanitation facilities and infrastructure including clean water, wastewater, drainage, and waste management. Improving access to sanitation in slum areas has faced notable financial challenges. Meanwhile, in the past few years, the making of rainbow villages or colorful villages is becoming a trend as an effort to improve the visuals of slum areas by painting houses. In further development, village visual improvement may convert the area into a tourism destination. The increase in social and economic value from being a tourism destination is expected to help stimulate the improvement of sanitation management in the village. Thus, the need to study rainbow village optimizing factors emerge. There are several rainbow villages in Bandung including Kampung Pelangi 200 and Kampung Cibunut Berwarna. Descriptive research design is used to compare and understand how the villages respond to the program. The survey research method is used to gather data. Based on the discussion, factors to be considered to optimize the aesthetical program and enable sanitation access acceleration are 1) Legality, 2) Institutional scheme, 3) Financial, and 4) Social.